AB0984 INTERSTITIAL LUNG DISEASE IN CHINESE JIA PATIENTS. (June 2019) - Ho, Assunta; Chan, Kate; Albert, LI
Abstract : Background: Rheumatic diseases and or medications (for example methotrexate) used to treat the underlying condition are associated with the development of interstitial lung disease (ILD). Development of ILD in subjects with juvenile idiopathic arthritis (JIA) is assumed to be rare, however, severe respiratory complications are increasingly reported in JIA patients. Objectives: To describe the prevalence of respiratory diagnoses and ILD in a group of Chinese JIA patients at a tertiary center. Methods: Retrospective chart review of JIA patients attending rheumatology clinic during 2012 to 2019 Results: Fifty-eight cases of JIA were identified. Thirty-three (57%) received DMARDs, majority were on methotrexate (MTx, 24, 73%) and sulphasalazine (SSZ, 14, 42%). Eleven (19%) were currently or previously on biologics (adalimumab 5, etanercept 5, anakinra 1, previous exposure: infliximab 1, etanercept and anakinra 1). Respiratory diagnosis was made in 11 (19%) patients. There were 2 (3.4%) cases of ILD diagnosed during the study period (see below). The rest were asthmatics. Among them, 9 were on DMARDs [MTx 8(89%), SSZ 4(44%), leflunomide 2(LEF), hydroxychloroquine 1(HCQ)] or biologics [Etanercept 3(33%), adalimumab 1, tocilizumab and anakinra 1(sequential use)]. Four subjects were on combination DMARDs [MTx&SSZ in 2, 1 each for MTx+LEF+HCQ+SSZ (sequential combination)& MTx+LEF]. Three received combination DMARDs and biologics (1 each for MTx+adalimumab, MTx+etanercept & MTx+anakinra). Cases of ILD One was a SJIA patient diagnosed at 2 years old. She failed methotrexate, etanercept & tocilizumab (infusion reaction). She was on low dose prednisolone, methotrexate and anakinra when she presented to us with acute right heart failure requiring ICU care 3 years after diagnosis. Advanced clubbing was noted (fig 1 ). HRCT thorax on presentation showed severe interstitial lung disease with marked fibrosis and traction bronchiectasis (fig 2 ). She was diagnosed acute on chronic cor pulmonale and pulmonary hypertension secondary to ILD. The other was an oligoarticular JIA patient, diagnosed at 2 years old. She was refractory to intra-articular steroid injections and combination DMARDs including MTx, SSZ, LEF & HCQ. Arthritis was controlled by Etanercept. At 12 years of age, she started to have chest pain. Lung function test showed restrictive lung pattern. HRCT thorax showed pulmonary fibrosis. Conclusion: From this Chinese cohort we identified 2 cases of ILD. They did not present with any symptoms until advanced stage or when complications set in. Both were very young at diagnosis and were difficult to control, as evidenced by the use of multiple DMARDs and biologics including methotrexate, IL6 and IL1 blockade. The causes of ILD are believed to be multifactorial. For severe case, prognosis is poor 1 . Although rare, methotrexate induced pneumonitis do occur. Symptoms of ILD may not be obvious until late stage. Clinical examination alone is not sensitive enough to detect disease progression. Asthma is common, as in this cohort, and may further complicated the assessment. It is recommended in the recent SHARE initiative on JSLE to screen for lung disease 2 . We believe it should be performed in JIA patients as well. 6 minute walk test is a noninvasive way to assess cardiopulmonary functional status and is validated in children 3 . Patients with unexplained chest symptoms or impaired lung function should be referred to pulmonologist for further assessment. References: [1] Kimura Y, et al. Pulmonary Hypertension and other potentially fatal pulmonary complications in systemic juvenile idiopathic arthritis. Arthritis Care Res2013;65(5):856-52 [2] Groot N, et al. European evidence-based recommendations for diagnosis and treatment of childhood-onset systemic lupus erythematosus: the SHARE initiative. Ann Rheum Dis2017;76:1788-96 [3] Li AM, et al. The six-minute walk test in healthy children: reliability and validity. Eur Respir J2005;25:1057-60 Disclosure of Interests: None declared